Language acquisition, linguistic variation, and sociolinguistic development (Revista de Estudos da Linguagem, 2024)
This paper discusses the relation between variable input and sociolinguistic development in mother-tongue acquisition process. During language acquisition, children can acquire a linguistic system that differs – to some degree – from that of their primary caregivers. This fact emphasizes the close relationship that exists between language acquisition, linguistic variation and linguistic change. However, the presence of variation in primary linguistic data does not guarantee linguistic change. At this point, it is worthy to say that, although the attribution of social values to linguistic forms is a particular phase of the acquisition process, the perception of linguistic variability per se does not seem to be sufficient for such attribution to be made by children. By adopting the psycholinguistic assumptions, this paper aims at discussing some relevant aspects of language acquisition, linguistic variation and sociolinguistic development by analyzing the phenomenon of variable nominal and verbal number agreement in Brazilian Portuguese. Naturalistic data were analyzed in order to verify the input received by children and their own linguistic production. Formal education – and its normative effects in language –, speaker identity and the different dimensions of communicative interaction, as well as methodology issues, seem to be crucial for a deeper understanding of the topics under discussion.